1992
DOI: 10.1177/0093854892019002004
|View full text |Cite
|
Sign up to set email alerts
|

Personal Precautions to Violence in Prison

Abstract: Although studies have documented increased levels of violence in U.S. prisons, little attention has been given to how this violence shapes inmate behaviors and life-styles. This article presents results from a survey of 300 adult males incarcerated in a maximum-security facility, providing data on the types, prevalence, and social correlates of personal precautions to violence. A factor analysis of responses revealed two distinct dimensions of precautionary behavior. The more fearful, older, and socially isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
110
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(118 citation statements)
references
References 4 publications
8
110
0
Order By: Relevance
“…Furthermore, much of the research that addresses bullying per se within prisons has been confined to the United Kingdom, with the exception of Connell and Farrington [1996], who addressed bullying among male young offenders at an open-custody facility in Canada. Research conducted outside the United Kingdom has been concerned primarily with general issues of violence and victimisation between inmates as opposed to bullying [e.g., McCorkle, 1992;Mutchnick and Fawcett, 1990;Toch, 1992].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, much of the research that addresses bullying per se within prisons has been confined to the United Kingdom, with the exception of Connell and Farrington [1996], who addressed bullying among male young offenders at an open-custody facility in Canada. Research conducted outside the United Kingdom has been concerned primarily with general issues of violence and victimisation between inmates as opposed to bullying [e.g., McCorkle, 1992;Mutchnick and Fawcett, 1990;Toch, 1992].…”
Section: Introductionmentioning
confidence: 99%
“…Prisoners may also feel anxious about their personal safety due to the companionship of unfamiliar and potentially dangerous others. This anxiety, combined with a scarcity of available goods and drug use, can increase the pressures prisoners feel to engage in confrontations so as to protect themselves and their possessions from harm ( Sykes 1958 ;McCorkle 1982 ;Crewe 2005 b ). In this way, the prison environment can lead prisoners to engage in confrontations as they attempt to deter others from exploiting them.…”
mentioning
confidence: 99%
“…For those already associating ' toughness ' with ' manliness ' , the use of aggression to demonstrate their masculinity may be reinforced ( Sim 1994 ;Crewe 2006). For others, this can lead them to ' put on a front ' while in prison so as to appear ' tough ' and deter victimization ( Sykes 1958 ;McCorkle 1982 ;Sim 1994 ;Sabo et al 2001 ;Edgar et al 2003 ). Hence, male prisoners may engage in confrontations in order to ensure their personal safety, and that of their possessions, as well as demonstrate or reaffi rm their identity as a ' man ' .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although reported similar rates for physical assault among male and female inmates, physical assaults against males were more likely to involve the use of a weapon. Indeed, it is recognized that a significant number of inmates appear to carry weapons (McCorkle, 1992). Among staff-on-inmate physical assaults, a recent study reported that 24.6%…”
Section: The Contribution Of Correctional Officers To the Social Envimentioning
confidence: 99%